Asiaticoside Attenuates Chronic Restraint Stress-Induced Hippocampal CA1 Neuronal Ferroptosis via Activating BDNF/Nrf2/GPX4 Signaling Pathway - Zhou A; Feng HY; Fan CN; Wang J; Yuan ZY; Xu GH; Li CF; Huang WF; Yi LT (Drug Design, Development and Therapy)
An Zhou,1– 3 Hao-Yinghua Feng,4 Chu-Ning Fan,3 Jun Wang,3 Zhong-Yu Yuan,3 Guang-Hui Xu,5 Cheng-Fu Li,6 Wei-Feng Huang,1 Li-Tao Yi3,7,8 1Department of Gastroenterology and Hepatology, The First Affiliated Hospital of Xiamen University, School of Medicine, Xiamen University, Xiamen, Fujian Province, 361003, People’s Republic of China; 2School of Pharmaceutical Sciences, Fujian Provincial Key Laboratory of Innovative Drug Target Research, Xiamen University, Xiamen, Fujian Province, 361102, People’s Republic of China; 3Department of Chemical and Pharmaceutical Engineering, College of Chemical Engineering, Huaqiao University, Xiamen, Fujian Province, 361021, People’s Republic of China; 4College of Pharmacy, Guangzhou University of Chinese Medicine, Guangzhou, Guangdong province, 510006, People’s Republic of China; 5Xiamen Medicine Research Institute, Xiamen, Fujian Province, 361008, People’s Republic of China; 6Xiamen Hospital of Traditional Chinese Medicine, Xiamen, Fujian Province, 361009, People’s Republic of China; 7Institute of Pharmaceutical Engineering, Huaqiao University, Xiamen, Fujian Province, 361021, People’s Republic of China; 8Fujian Provincial Key Laboratory of Biochemical Technology, Huaqiao University, Xiamen, Fujian Province, 361021, People’s Republic of ChinaCorrespondence: Li-Tao Yi, Department of Chemical and Pharmaceutical Engineering, Huaqiao University, 668 Jimei Avenue, Xiamen, Fujian Province, 361021, People’s Republic of China, Email litaoyi@hqu.edu.cn Wei-Feng Huang, Department of Gastroenterology and Hepatology, The First Affiliated Hospital of Xiamen University, 55 Zhenhai Road, Xiamen, Fujian Province, 361003, People’s Republic of China, Email hwf0625@xmu.edu.cnPurpose: Ferroptosis, characterized by iron-dependent lipid reactive oxygen species accumulation, plays a critical role in the pathophysiology of depression. Our research aims to elucidate the potential antidepressant mechanisms of asiaticoside, a bioactive compound known for its neuroprotective and immunomodulatory properties.Methods: The antidepressant-like properties of asiaticoside in a model of chronic restraint stress (CRS)-induced depression in mice, with a particular focus on its interaction with ferroptosis-related pathways.Results: The behavioral results revealed that asiaticoside significantly ameliorated CRS-induced depressive symptoms, as evidenced by increased sucrose preference and reduced immobility time. At the molecular level, asiaticoside enhanced the expression of brain-derived neurotrophic factor (BDNF), phosphorylated tropomyosin receptor kinase B (pTrkB), phosphorylated nuclear factor erythroid 2-related factor 2 (pNrf2), glutathione peroxidase 4 (GPX4), and solute carrier family 7 member 11 (SLC7A11), indicating its neuroprotective and antioxidative effects. In addition, asiaticoside suppressed the expression of ferroptosis markers, including ferritin light chain (FLC) and transferrin receptor only in CA1 region. Transmission electron microscopy (TEM) further confirmed that asiaticoside preserved mitochondrial integrity in CA1 neuronal cells.Conclusion: In conclusion, our findings suggest that asiaticoside exerts its antidepressant-like effects through the modulation of BDNF/Nrf2/GPX4 signaling pathway against neuronal ferroptosis in the hippocampal CA1 region.Keywords: asiaticoside, antidepressant, ferroptosis, BDNF, Nrf2, GPX4